Peran Prudence dan Komisaris Independen Sebagai Moderasi Pengaruh Intellectual Capital dan Board Diversity Terhadap Green Intellectual Capital - Hakki, Tandry; Yanti, Yanti; Vivi, Vivi (Dinasti Research, 2024)
The need to improve the quality of presentation in annual reports is not only in the form of financial information but also non-financial information. This information is expected to increase stakeholder trust and reduce the level of risk and uncertainty faced by investors. The types of information provided by companies in annual reports can be classified into two, namely mandatory information and voluntary information. One of the voluntary information is information about green intellectual capital. This study aims to test the effect of Intellectual Capital, Board of Diversity on Green Intellectual Capital moderated by Prudence and Independent Commissioners. This study took the research population in energy sector companies. The type of data used in this study is primary data in the form of company financial reports that are used as samples. The research method used in this study is a quantitative research method. The sample was selected using the purposive sampling method. For hypothesis testing, this study uses multiple linear regression analysis. Based on the results of this study, it shows that Intellectual Capital has a significant effect on Green Intellectual Capital, Board Diversity does not affect Green Intellectual Capital, Independent Commissioners strengthen the influence of Intellectual Capital on Green Intellectual Capital, Prudence strengthens the influence of Intellectual Capital on Green Intellectual Capital. Board Diversity does not strengthen the influence of Intellectual Capital on Green Intellectual Capital, Board Diversity does not strengthen the influence of Intellectual Capital on Green Intellectual Capital.